Biomimetic Growth Of Hydroxyapatite On Kenaf Fibers - Saiful Izwan, Abd Razak; Izzati Fatimah, Wahab; Mohammed Rafiq, Abdul Kadir; Ahmad Zahran, Md Khudzari; Abdul Halim, Mohd Yusof; Farah Nuruljannah, Dahli; Nadirul Hasraf, Mat Nayan; T. Joseph Sahaya, Anand (BioResources.com, 2016)
Biomimetic hydroxyapatite (HA) growth on mercerized kenaf fiber (KF) was achieved by immersion in a simulated body fluid (SBF) solution with the addition of a chelating agent. An electron micrograph revealed uniform HA layers on the KF within 14 days of immersion with significant vibrational peaks of HA components. The tensile tests showed no significant drops in the unit break of the modified fibers. This new bone-like apatite coating on KF can be useful in the field of bone tissue engineering. The key motivation for this new approach was that it utilizes the abundantly available kenaf plant resource as the biobased template.